EXAMINATION OF BOOKS AND RECORDS FOR USE IN A CRIMINAL TRIAL. - Baker, Joe M. (The Accounting Review, 1942)
Increasing activities of the various Federal agencies in examining, investigating, and regulating commerce and industry have no doubt taken away from the accounting profession some of the work formerly performed by public accountants. The profession as a whole has not suffered from the loss of such engagements, but on the contrary, has immeasurably benefited in other ways from these increasing activities by the Federal government. Private industry and individuals are seeking more and more the expert assistance of skilled accountants in interpreting and following the laws, rules, and regulations of the various governmental agencies affecting accounting principles and practices. Many practicing accountants are now called upon to testify before governmental agencies on behalf of their clients, and consider such work as professional routine. It is likely that Federal agencies have taken the responsibility of examining and investigating many cases of an accounting nature, which were formerly under the control, and supervision of accountants engaged in private practice, or was not examined at all.